Bark : [large type] stories - Moore, Lorrie (Thorndike Press large print basic series., 2014)
In eight stories, Lorrie Moore explores the passage of time and summons up its inevitable sorrows and hilarious pitfalls. In "Debarking," a newly-divorced man tries to keep his wits about him as the United States prepares to invade Iraq. In "Foes," a political argument goes grotesquely awry as the events of 9/11 unexpectedly manifest themselves at a fund-raising dinner in Georgetown. In "The Juniper Tree," a teacher visited by the ghost of her recently-deceased friend is forced to sing "The Star-Spangled Banner" in a kind of nightmare reunion. And in "Wings," we watch the inevitable unraveling of two once-hopeful musicians, neither of whom held fast to their dreams nor struck out along other paths, as Moore depicts the intricacies of dead-ends-ville and the workings of regret. Here are people beset, burdened, buoyed; protected by raising teenage children; dating after divorce; facing the serious illness of a longtime friend; coping with large dislocation in their lives and risking a new path.